Gambaran Kesiapan Karyawan untuk Kembali Bekerja di Kantor: Perubahan dari WFH ke WFO - Johannes Danny Wirapratama; Rayini Dahesihsari (Jurnal Ilmiah Psikologi MIND SET, 2022)
After almost 2 years of COVID-19 pandemic hits Indonesia, Work From Home (WFH) has been applied as the new way of working and the employees have now already adapted with WFH. However, in this new normal era, employees are expected to return to the office as in Work From Office (WFO) and it turns out most of them are not ready. This study aimed to describe employee’s readiness to return to the office. This study uses the concept of readiness for change. This study collected 200 participants that are working from home during the pandemic. Using 21 items of readiness for returning to the office questionnaire, consisting 4 dimensions, which are appropriateness, change specific efficacy, management support, and personal valance. Descriptive statistics were applied for data analysis. The findings showed that, in general, participants are showing the readiness for returning to the office. If viewed from all four dimensions, it shows that they’re ready to return to the office; however appropriateness and personal valance dimension could be optimized by increasing employee’s awareness the importance of returning to the office. In addition, there was a significant difference for participants on the line of work groups, tenure, salary, employee’s performance during WFH, and how long they had been working from home.